2020
DOI: 10.4142/jvs.2020.21.e18
|View full text |Cite
|
Sign up to set email alerts
|

Feline vocal communication

Abstract: Cat vocalizes to communicate with another and express their internal states. The vocal repertoire of the cat is wide and up to 21 different vocalizations have been described in the literatures. But it is more than probable that the repertoire contains more types of vocalizations. An ethogram was created in this paper describing the actual known vocalisations of the domestic cat based on an auditory classification. However, the audiogram allows also a visual classification which can increase the accuracy of voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Meowing is a common and mainly human-directed vocalization [ 34 , 35 , 42 ]; thus, in principle, it should represent a useful mean for cats to communicate their emotional states to humans. Furthermore, previous studies showed that meows emitted in these three different contexts can be successfully discriminated on the basis of a series of acoustic parameters [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meowing is a common and mainly human-directed vocalization [ 34 , 35 , 42 ]; thus, in principle, it should represent a useful mean for cats to communicate their emotional states to humans. Furthermore, previous studies showed that meows emitted in these three different contexts can be successfully discriminated on the basis of a series of acoustic parameters [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although research on domestic cat behavior and cognition is growing [ 37 ], cat cognitive and communicative skills have been far less investigated than those of dogs, and the literature on the cat–human relationship and communication is more sparse and limited [ 10 , 38 ]. Only a handful of studies have investigated cat vocalizations and the characteristics of cat–human communication [ 39 , 40 , 41 , 42 , 43 ] and little is known about the human ability to recognize and classify the context and the possible emotional content of cat-to-human vocalizations [ 44 , 45 , 46 ]. However, understanding the extent of the effectiveness of the reciprocal communication between cats and humans is not only theoretically interesting but also relevant for cat welfare, since cats, like dogs, live in close contact with their human social partners and depend on them for health, care, and affection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations